COMPARISON OF THE PHYSICAL QUALITY OF ELEPHANT GRASS SILAGE (PENNISETUM PURPUREUM) WITH THE ADDITION OF 2 TYPES OF ADDITIVES - Permadi, I Gede Wempi Dody Surya; Gunawan, Gunawan; Paradhipta, Dimas Hand Vidya; Noviandi, Cuk Tri (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Forage availability is a key determinant of ruminant livestock productivity, particularly in tropical regions where seasonal variability often limits consistent feed supply. Elephant grass (Pennisetum purpureum) is widely cultivated due to its high biomass yield, adaptability, and ease of cultivation. However, its utilization as fresh forage is constrained by high moisture content, rapid nutrient deterioration, and seasonal availability. This riview is combinating research and secondary date.     This research was conducted in March - October 2025, in Sleman Regency, Indonesia. The aim of this study was to compare the physical quality of elephant grass silage with Aspergillus niger and Lactobacillus plantae additives.  Experienced panelists were selected to observe the physical quality of both types of silage.  Silage technology offers an effective solution by preserving forage through anaerobic fermentation mediated by lactic acid bacteria, enabling long-term storage and year-round feed availability. Despite its potential, elephant grass presents challenges as a silage material, notably low water-soluble carbohydrate content and high fiber levels, which can impede optimal fermentation. The incorporation of feed additives, such as carbohydrate sources, microbial inoculants, and other natural or chemical additives, is therefore necessary to enhance fermentation quality. These additives promote rapid pH decline, increase lactic acid production, inhibit spoilage microorganisms, and preserve nutritional value. The development of elephant grass silage technology using appropriate feed additives is essential to produce high-quality silage, support sustainable livestock production, and strengthen national feed security.